Pengaruh Model Pembelajaran Inkuiri Menggunakan Media Animasi Terhadap Kemampuan Pemecahan Masalah Pada Materi Sistem ekskresi Kelas VIII MTs Swasta Al Washliyah Serbelawan - Humairoh T, Siti; Tridelpina Purba, Sumarny; Polemon Hutagaol (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This study aims to determine the effect of the inquiry learning model using animation media on problem-solving abilities in the excretory system material of class VIII MTs Swasta Al Washliyah Serbelawan. The population in this study was all class VIII consisting of 3 classes with a total of 87 students. Sampling was done by Cluster Random Sampling. This research instrument was used to see problem-solving abilities in the excretory system material using tests and questionnaires. From the results of the t (1) test data analysis, t count (5.213) ≥ t table (2.005) at a significant level of α = 0.05 with degrees of freedom dk = 28 + 28-2 = 54, then H0 is rejected and Ha is accepted, meaning that problem-solving abilities have a significant influence if learning is carried out using the inquiry learning model. Meanwhile, the results of the t-test data analysis (2) obtained t count (5.942) ≥ t table (2.005) so H0 is rejected and Ha is accepted, meaning that problem-solving ability has a significant influence if learning is carried out using the inquiry learning model with animation media. Furthermore, the results of the F-test data analysis obtained F count is greater than F table, namely F count (5.072) > F table (3.172), so it can be concluded that the hypothesis H0 is rejected and Ha is accepted, meaning there is an effect of the inquiry learning model using animation media on problem-solving ability in the human excretory system material for class VIII MTs Swasta Al Washliyah Serbelawan.